1994
DOI: 10.1002/pro.5560031230
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group protein, hmg‐1, contains insignificant glycosyl modification

Abstract: Abstract:High mobility group protein-1 (HMG-1) is a ubiquitous, highly conserved, and abundant nuclear protein. Recent findings suggest that HMG-1 may serve as a DNA chaperone protein and play a role in the regulation of transcription. There is a mounting interest in elucidating the mechanism by which HMG-1 protein takes part in these activities. HMG-1 has been reported to undergo an extensive array of posttranslational modifications, including glycosylation. We extend the earlier findings on the glycosylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…There are reports on nuclear and cytoplasmic glycosylation. Several studies have also strongly indicated that high-mobility-group proteins, important structural components of chromatin, are glycoproteins [48]. The increased fucosylation of proteins with transcriptional regulation functions would increase the protein size; this could become an issue when the proteins are being transported inside the nucleus to perform their functions.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports on nuclear and cytoplasmic glycosylation. Several studies have also strongly indicated that high-mobility-group proteins, important structural components of chromatin, are glycoproteins [48]. The increased fucosylation of proteins with transcriptional regulation functions would increase the protein size; this could become an issue when the proteins are being transported inside the nucleus to perform their functions.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 is also able to undergo glycosylation, although the amount is insignificant and the function is unclear (Chao et al, 1994). …”
Section: Hmgb1 Post-translational Modificationmentioning
confidence: 99%